2019
DOI: 10.1128/aem.02605-18
|View full text |Cite
|
Sign up to set email alerts
|

The Ferredoxin-Like Protein FerR Regulates PrbP Activity in Liberibacter asiaticus

Abstract: In Liberibacter asiaticus, PrbP is an important transcriptional accessory protein that regulates gene expression through interactions with the RNA polymerase β-subunit and a specific sequence on the promoter region. The constitutive expression of prbP observed upon chemical inactivation of PrbP-DNA interactions in vivo indicated that the expression of prbP was not autoregulated at the level of transcription. This observation suggested that a modulatory mechanism via protein-protein interactions may be involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…The selected proteins were fused to two non‐functional but complementing β‐galactosidase truncations (Δα and Δω). The β‐galactosidase activity driven by the protein–protein recognition between both non‐β‐galactosidase parts of the chimaeras allowed analysis of protein–protein interactions (Borloo et al ., 2007; Pan et al ., 2019). The sequences encoding for RpoH, PleD, VisN, VisR, CtrA, MocR, MucR and PrbP were cloned and fused to the β‐galactosidase truncations Δα and Δω on plasmids pB2HΔα and pB2HΔω respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected proteins were fused to two non‐functional but complementing β‐galactosidase truncations (Δα and Δω). The β‐galactosidase activity driven by the protein–protein recognition between both non‐β‐galactosidase parts of the chimaeras allowed analysis of protein–protein interactions (Borloo et al ., 2007; Pan et al ., 2019). The sequences encoding for RpoH, PleD, VisN, VisR, CtrA, MocR, MucR and PrbP were cloned and fused to the β‐galactosidase truncations Δα and Δω on plasmids pB2HΔα and pB2HΔω respectively.…”
Section: Resultsmentioning
confidence: 99%
“…asiaticus RNA polymerase in a dose‐dependent manner. FerR was also found to improve the affinity of PrbP for rplK , in vitro (Pan et al ., 2019). Using small‐molecule screening, tolfenamic acid (TA) was identified as a molecule that binds PrbP and disrupts interactions with the rplK promoter, in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we demonstrate in vivo that CarD activity leads to diverse gene expression outcomes and does not solely act as a transcriptional activator. Importantly, CarD homologs are conserved in many bacterial phyla (8,9), and regulate transcription to mediate diverse processes including stress responses, cell division, and metabolic homeostasis (10)(11)(12)(13). Therefore, these studies shed light on the maintenance of optimal gene expression patterns broadly across bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In mycobacteria, carD expression is induced by genotoxic, oxidative, starvation, and antibiotic stresses (8), suggesting that CarD may serve as a stress-responsive transcriptional regulator in addition to its essential function. CarD homologs in other bacteria have also been shown to respond to diverse environmental stimuli (10,11) and regulate critical processes such as metabolic homeostasis and cell division (12,13).…”
mentioning
confidence: 99%
“…The genes encoding those proteins were cloned, purified, characterized and successfully screened against the Prestwick chemical library (Prestwick Chemical, France) to identify ligands with high binding affinity. Using this methodology, we successfully identified small molecules that inhibit the activity of specific transcription factors [12][13][14][15][16] . Based on these previously published data, we performed field trials using benzbromarone and tolfenamic acid, the small molecules that were found to inhibit activity of the regulatory proteins LdtR and PrbP.…”
mentioning
confidence: 99%